Pengembangan Instrumen Digital Literacy Assessment Scale (DLAS) Untuk Mengukur Kemampuan Literasi Digital Mahasiswa - Anggi Ristiyana Puspita Sari; Suandi Sidauruk; Ruli Meiliawati; Maya Erliza Anggraeni (FKIP Universitas Palangka Raya, 2021)
The COVID-19 pandemic requires lecturers to change learning strategies through online learning. The use of technology which has grown exponentially in the world of education requires students to be proficient in using technology in finding information as a source of knowledge. To be able to prepare competitively students in this 4.0 education era, an instrument is needed to find out to what extent students' digital literacy abilities are. This research is development research (R&D) which aims to develop a Digital Literacy Assessment Scale (DLAS) instrument to measure students' digital literacy skills. The procedure of this research includes determining the construct and specifications of the instrument, writing the items, and analyzing the items. Based on the results, the DLAS instrument has a total of 52 items consisting of 3 aspects including access to information (access), student involvement in academic activities (behavioral engagement), and socio-emotional (socio-emotional). The results of content validity carried out by 5 expert judgments showed that the DLAS instrument was proven to be content valid with the acquisition of Aiken's V index of 0.87.